Nutritive value of crop residue and byproducts of groundnuts - Reed, J.D. (International Crops Research Institute for the Semi-Arid Tropics, 1987)
Discusses the nutritive value of the crop residue and byproducts from groundnuts in relation to the potential influence that crop improvement programs could have on improving their utilization by livestock. Compares nutritional composition and in vitro digestibility of groundnut cake, cottonseed cake, and higer-seed cake; as well as groundnut hulls, dust and skin.